Discovery of the Hedgehog Pathway Inhibitor Pipinib that Targets PI4KIIIß. Issue 46 (4th October 2019) - Kremer, Lea; Hennes, Elisabeth; Brause, Alexandra; Ursu, Andrei; Robke, Lucas; Matsubayashi, Hideaki T.; Nihongaki, Yuta; Flegel, Jana; Mejdrová, Ivana; Eickhoff, Jan; Baumann, Matthias; Nencka, Radim; et al.
Abstract: The Hedgehog (Hh) signaling pathway is crucial for vertebrate embryonic development, tissue homeostasis and regeneration. Hh signaling is upregulated in basal cell carcinoma and medulloblastoma and Hh pathway inhibitors targeting the Smoothened (SMO) protein are in clinical use. However, the signaling cascade is incompletely understood and novel druggable proteins in the pathway are in high demand. We describe the discovery of the Hh‐pathway modulator Pipinib by means of cell‐based screening. Target identification and validation revealed that Pipinib selectively inhibits phosphatidylinositol 4‐kinase IIIβ (PI4KB) and suppresses GLI‐mediated transcription and Hh target gene expression by impairing SMO translocation to the cilium. Therefore, inhibition of PI4KB and, consequently, reduction in phosphatidyl‐4‐phosphate levels may be considered an alternative approach to inhibit SMO function and thus, Hedgehog signaling. Abstract : Cell‐based screening identifies a thieno[3, 2]pyrimidine derivative as an inhibitor of Hedgehog signaling by selective inhibition of phosphatidylinositol 4‐kinase IIIβ (PI4KB), reduction of PI4P levels and prevention of Hedgehog‐mediated ciliary localization of Smoothened. Thus, PI4KB may be a relevant target protein for inhibition of Hedgehog signaling.